Moral Development as a Regulatory Strategy for Nafs al-Lawwamah: An Islamic Psychological Perspective - Hidayat, Muslim (Prodi Studi Agama-Agama, 2026)
Nafs al-lawwamah is an interesting study to discuss. Because the concept of nafs al-lawwamah requires two scientific studies, namely between Islamic psychology and Islamic scholarship. However, with the many concepts in the two disciplines, a study specification is needed so that a detailed and comprehensive study is produced. In addition, seeing the concept of nafs al-lawwamah which is closely related to how individuals can direct their souls in the right direction, training or habituation is needed which is also a study in psychology. One of them is moral development which is one of the concepts of soul development, where this concept describes a blend of psychology and Islamic scholarship. Because of the continuity of the concept of training or mental development of individuals and even certain groups through moral development, the author conducted this research. Therefore, this study aims to find out more deeply about the concept of nafs al-lawwamah, the concept of moral development, the steps for moral development, and the effectiveness of the concept. The method used in this research is a literature study with library research, and the sources used are journals and documents relevant to the study in this research. From the sources obtained, an analysis related to the research objectives was carried out. The results of this study are that it can be seen the steps of moral development will have positive implications for the nafs al-lawwamah, so that it will become a nafs al-mutmainnah